Respuesta :

Answer:

x = 1/3 or 0.333333

Step-by-step explanation:

Simplify to the left side.

Simplify each term.

Multiply 3 by -2

-6 + 6 (x + 1) -2 = 0

Apply the distributive property.

-6 + 6x + 6 * 1 - 2 = 0

Multiply 6 by 1.

-6 + 6x + 6 - 2 = 0

Simplify the expression.

Add -6 and 6.

6x + 0 - 2 = 0

Add 6x and 0.

6x - 2 = 0

Add 2 to both sides of the equation.

6x = 2

Divide each term by 6 and simplify.

Divide each term in 6x - 2 by 6.

(6x) / 6 = 2 / 6

Reduce the expression by canceling the common factors.

x = 2/6

Reduce the expression by canceling the common factors.

x = (2(1)) / 6

Cancel the common factors.

x = (2 * 1) / (2 * 3)

The result can be shown in multiple forms.

Exact form:

x = 1/3

x = 0.33333333